Stigmatizing attitudes and predictors of empathy toward mentally ill patients among psychiatric and mental health nurses - Warda Elshahat Hamed; Ashjan Saeed Babegi; Hind Abdallah Modawi Elamin; Nesma Ahmed Kamel; Ana Maria Escolano-Castillo; Hamad Ghaleb Dailah; Rania Rabie Eletreby (BMC Nursing)
Abstract Background Nurses’ personal experiences and relationships with patients suffering from mental disorders are linked to bias and discrimination. A notable association exists between the desire to work in mental health settings and prejudice, as well as between educational attainment and stereotypical beliefs. Mental health nurses need to possess a strong capacity for empathy and positive attitudes towards patients with mental disorders. Aim of the study This study aimed to investigate predictors of empathy and stigmatizing attitudes toward mentally ill patients among psychiatric and mental health nurses. Method A descriptive correlational cross-sectional research design was used in this study to assess levels of empathy and stigma and to identify predictors of empathy as well as relationships between variables. A convenience sample of 122 psychiatric and mental health nurses was selected as respondents from two settings: the psychiatric inpatient and outpatient departments of Mansoura University Hospitals and Demera Mental Health Hospital which are situated in Dakahlia Governorate in the Delta area, Egypt. Tools Three instruments were used in this study, including a socio-demographic questionnaire, the Opening Mind Scale for Health Care Providers (OMS-HC), and the Perth Empathy Scale (PES). Results This study found that nearly three-quarters (70.5%) of nurses held low stigmatizing attitudes toward mental illness, while about one-third (29.5%) displayed high stigmatizing attitudes. Most participants (64.8%) scored moderately on the Perth Empathy Scale. A significant association was identified between higher education in psychiatric nursing, years of experience, and increased stigmatizing attitudes toward mental illness. Additionally, a negative relationship was found between stigmatizing attitudes and empathy, indicating that higher stigma was linked to lower empathy scores. The results also suggest that positive attitudes toward mentally ill patients are associated with higher levels of empathy. Conclusion Positive attitudes are linked to higher education, more experience, and greater empathy. Higher education and years of experience, along with a positive attitude predicted higher levels of empathy toward mentally ill patients. Targeted interventions, such as workshops, role-playing, and Cognitive Behavioral Therapy (CBT) programs, are recommended to reduce stigma and enhance empathy among psychiatric nurses. Clinical trial number Not applicable.